2020
DOI: 10.1016/j.marpetgeo.2019.104205
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model for glaciogenic reservoirs: From landsystems to reservoir architecture

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 291 publications
(524 reference statements)
0
7
0
Order By: Relevance
“…This and the shallow gas indicators at the clinoform truncations suggest that despite the glacial origin, sandstones are present within these features that could facilitate CO 2 migration up‐dip (Figure 13). Given the features’ glacial origin, their general sandstone abundance is likely to be low (Kurjanski et al., 2020) and the sandstone quality is likely to be poorer in terms of porosity and permeability than the channel and lobe features from the ESP. As such, it could be suggested that their sealing ability is greater than proposed here.…”
Section: Discussionmentioning
confidence: 99%
“…This and the shallow gas indicators at the clinoform truncations suggest that despite the glacial origin, sandstones are present within these features that could facilitate CO 2 migration up‐dip (Figure 13). Given the features’ glacial origin, their general sandstone abundance is likely to be low (Kurjanski et al., 2020) and the sandstone quality is likely to be poorer in terms of porosity and permeability than the channel and lobe features from the ESP. As such, it could be suggested that their sealing ability is greater than proposed here.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the morphologies of the flat‐topped hills and associated secondary landforms, the hills were interpreted as ice‐contact Gilbert‐type deltas deposited in a lake with water depths of 35 to 60 m above the present‐day land surface (Gilbert, 1885, 1890; Glückert, 1986; Lønne, 1995; Palmu, 1999; Saarnisto & Saarinen, 2001; Thomas & Chiverrell, 2006; Dietrich et al ., 2017b; Kurjanski et al ., 2020). Meltwater and sediments were supplied to the ice margin chiefly via subglacial/englacial meltwater channels and deposited under water, proximal to the grounding line as ice‐contact, subaqueous fans (Powell, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…16). This can be magnified when the deltas are buried or when reservoir pressures are relatively low, such as in the glaciogenic Pleistocene sediments of the North Sea (Le Heron et al ., 2006; Hirst, 2012; Martin et al ., 2012; Ottesen et al ., 2012; Rose et al ., 2016; Kurjanski et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations